A cross-country comparison of pig production systems performance: Evidence from EU countries - Ricardo Troncoso; Juan Cabas; Bouali Guesmi; José María Gil (Economía Agraria y Recursos Naturales)
This study estimates and analyze the technical efficiency of pork farms from five EU countries. The Generalized True Random-effects (GTRE) model was used to differentiate between persistent and transitory technical efficiency. The results show that elasticities are robust to various specifications. Spanish farms show the highest average efficiency score. In Denmark, Germany, France, and Poland, the most significant opportunities for growth are found in transitional efficiency. The degree of productive specialization in the five countries has a positive impact in the efficiency. In Denmark, Germany, and France, persistent efficiency has a positive association with the fraction of paid labor.